A randomised controlled trial of the effects of screening for ulcer-type dyspepsia. Issue 3 (September 1982) - Bulpitt, C J; Rowntree, R K; Semmence, A
Abstract : One hundred and ninety-nine male London office workers with dyspeptic symptoms elicited by a self-administered questionnaire were randomly allocated to intervention and control groups to assess the potential benefits of screening. The members of the intervention group were interviewed and examined, and those men who were considered to have a possible or probable peptic ulcer received a barium meal examination (53%). At the clinical interview the intervention group were advised against both smoking and drinking alcohol. Eighteen months later both groups were recalled for interview and examination and their sickness absence in the intervening period was assessed. The intervention group did not alter their cigarette consumption but did reduce their alcohol intake by an average of 10%. The control group increased their alcohol intake by 20%. Both groups tended to improve symptomatically, and there were no differences in symptoms between the groups at the end of the study. Sickness absence was not affected by the intervention. It is concluded that screening for ulcer-type dyspepsia is not justifiable in male London office workers.